Periodic-surface-lattice cavities for millimetre-wave Cherenkov sources - MacLachlan, A; Phipps, A; Robertson, C; Konoplev, I; Cross, A; Phelps, A (IEEE, 2013)
A two-dimensional (2D) periodic surface lattice (PSL) can be obtained by creating shallow periodic perturbations on a metal surface. When the individual lattice elements are synchronised by coupled volume and surface fields eigenmodes can be formed. Cavities based on a PSL of cylindrical topology have been studied and an analytical description of the dispersive properties of the cavity is presented. Under certain conditions these dispersive properties demonstrate the potential to create novel Cherenkov sources of coherent high power radiation. © 2013 IEEE.